(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
SUMMARY: 1. Introduction - 2. The SMOM self-qualification as full member of the international community: critical notes - 3. The nature and scope of the international legal subjectivity of SMOM - 4. The non-relevance of the canonical status and the relationship with the Holy See for the international subjectivity of SMOM - 5. Conclusions. ABSTRACT: The presence of the Order of Malta (acronym SMOM) on the international scene, because of its singularity, has been the subject of debate and discussion among scholars of international law as well as canon law. In fact, the SMOM’s juridical subjection to the Holy See because of its nature as a Catholic Religious Institute is a critical point under the traditional international legal theory that seems to be inconsistent with the Order’s international subjectivity. The aim of this study is to point out that, using a broad and modern notion of international subjectivity, there is no incompatibility between the canonical nature of the Order of Malta and its membership in the international community.